Global burden of pulmonary sarcoidosis from 1990 to 2021: a comprehensive analysis based on the GBD 2021 study - Cao, Jinming; Li, Haiqing; Yin, Xiaofei; Yang, Jianqiong; Pu, Lingling; Yang, Jing (Frontiers in Medicine, 2025)
Background and objectivePulmonary sarcoidosis is a chronic respiratory disease with a growing global burden. This study systematically assessed the epidemiological trends, disease burden, and associated factors of pulmonary sarcoidosis in 204 countries from 1990 to 2021 to provide evidence for its prevention and control.MethodsUtilizing Global Burden of Disease 2021 data, we analyzed the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of pulmonary sarcoidosis, along with age-standardized rates (ASR), across regions, sexes, and age groups. The association between the disease burden and socio-demographic index (SDI) was also explored.ResultsIn 2021, global incidence cases reached 390,000, with 43.07 million prevalence cases, 1.88 million deaths and 40.42 million DALYs. Despite decreases in ASR since 1990, absolute numbers rose. In 2021, Andean Latin America had the highest rates of incidence, prevalence, mortality and DALY, while Eastern Europe had the lowest. Nationally, the burden of the disease in 2021 is particularly significant in countries such as Mauritius and Italy. And disease burden was higher in males and the elderly. In addition, the DALY rate for pulmonary nodular disease showed a non-linear relationship with the SDI, with actual and expected DALY rates differing in most regions and countries.ConclusionPulmonary sarcoidosis poses a growing burden globally, with marked regional, demographic, and socioeconomic disparities. Targeted interventions, including early screening, improved healthcare access, and pollution control, are essential to reduce this burden and promote health equity.